2009
DOI: 10.1016/s0828-282x(09)70137-0
|View full text |Cite
|
Sign up to set email alerts
|

The utility of fragmented QRS complexes to predict significant intraventricular dyssynchrony in nonischemic dilated cardiomyopathy patients with a narrow QRS interval

Abstract: Fragmentation in the resting ECG is associated with significant intraventricular dyssynchrony in patients with nonischemic cardiomyopathy, narrow QRS and sinus rhythm. Fragmentation in ECG might be useful in identifying patients who could benefit from cardiac resynchronization therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…[10] The fQRS was defined as the presence of an additional R wave (R') or notching of R or S wave or the presence of fragmentation (more than one R') in at least two contiguous leads corresponding to a major coronary artery territory. [13] Although Electrocardiographic parameters were compared in patients who were exposed to high voltage (≥ 1000 volts) and low voltage (<1000 volts) subgroups (Table 3) Comparison of the percentage of patients who had abnormal ECG parameters between admission and follow-up ECGs is depicted in Table 4. The percentage of patients who had abnormal PWD, QTc, frontal QRS-T angle, Tp-e interval, Tp-e interval/QT and Tp-e interval/QTc were significantly higher on admission ECGs compared to follow-up ECGs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[10] The fQRS was defined as the presence of an additional R wave (R') or notching of R or S wave or the presence of fragmentation (more than one R') in at least two contiguous leads corresponding to a major coronary artery territory. [13] Although Electrocardiographic parameters were compared in patients who were exposed to high voltage (≥ 1000 volts) and low voltage (<1000 volts) subgroups (Table 3) Comparison of the percentage of patients who had abnormal ECG parameters between admission and follow-up ECGs is depicted in Table 4. The percentage of patients who had abnormal PWD, QTc, frontal QRS-T angle, Tp-e interval, Tp-e interval/QT and Tp-e interval/QTc were significantly higher on admission ECGs compared to follow-up ECGs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on this evidence, current class I recommendations were restricted to patients with complete LBBB. However, recent studies showed that fragmented QRS complexes in the electrocardiograms of patients with nonischemic dilated cardiomyopathy and narrow QRS complexes are associated with significant intraventricular dyssynchrony [58,59], and other studies suggested that fragmented QRS complexes might be useful in predicting response to CRT [60,61]. Ongoing studies are investigating the possibility of maximizing CRT benefits by refining ECG selection criteria [62].…”
Section: Patient Selectionmentioning
confidence: 99%
“…The fQRS was defined as the presence of an additional R wave (R') or notching of R or S wave or the presence of fragmentation (more than one R') in two contiguous leads corresponding to a major coronary artery territory. The fQRS was defined when it was present in at least two contiguous leads of those representing anterior (V 1 to V 5 ), lateral (I, aVL and V 5 , V 6 ), inferior (II, III, aVF), or posterior (V 1 , V 2 ) myocardial segments [5]. The fQRS was seen in more than one myocardial segment in some patients.…”
Section: Electrocardiogrammentioning
confidence: 99%
“…Fragmented QRS (fQRS) complexes are novel electrocardiographic signals which reflect altered ventricular conduction around regions of a myocardial scar. The fQRS is defined as the presence of slurred QRS complexes with various RSR' patterns without typical bundle branch block in two contiguous leads corresponding to a major coronary artery territory [5]. The detection of fQRS complexes in a routine 12-lead ECG is a marker for abnormal cardiac depolarisation.…”
Section: Introductionmentioning
confidence: 99%